2021
DOI: 10.1155/2021/5562667
|View full text |Cite
|
Sign up to set email alerts
|

MHD Flow of Thermally Radiative Maxwell Fluid Past a Heated Stretching Sheet with Cattaneo–Christov Dual Diffusion

Abstract: This study explains the impression of MHD Maxwell fluid with the presence of thermal radiation on a heated surface. The heat and mass transmission analysis is carried out with the available of Cattaneo–Christov dual diffusion. The derived PDE equations are renovated into ODE equations with the use of similarity variables. HAM technique is implemented for finding the solution. The importance of physical parameters of fluid velocity, temperature, concentration, skin friction, and heat and mass transfer rates are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 34 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…The opposite trend is noticed in the case of higher values of Q . To ensure the accuracy of the results and calculations displayed in Table 1, the results obtained are compared with the results of Mukhopadhyay 38 and Loganathan 20 . Fortunately, validation shows that the results were satisfactory and accurate.…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The opposite trend is noticed in the case of higher values of Q . To ensure the accuracy of the results and calculations displayed in Table 1, the results obtained are compared with the results of Mukhopadhyay 38 and Loganathan 20 . Fortunately, validation shows that the results were satisfactory and accurate.…”
Section: Results Analysismentioning
confidence: 99%
“…Chemically reacting Maxwell fluid flow over a convectively heated plate immersed in permeable media in presence of non-linear thermal radiation was reported by Hosseinzadeh et al 18 Mahanthesh et al 19 reported that the nanoparticle-concentration and fluid-temperature profile shows a progressive nature due to solar radiation. Recently, Loganathan et al 20 studied a Maxwell fluid past a stretching surface with Cattaneo–Christov dual diffusion and thermal radiation. They showed that fluid temperature enhanced for the progressive amount of the radiation parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Loganathan et al [60] have discussed the significance of Darcy-Forchheimer on third-grade fluid with entropy generation. Loganathan et al [61] have examined Maxwell fluid over a thermally radiative convective sheet. Karthik et al [62] have investigated the importance of zero and non-zero mass fluxes of bioconvection viscoelastic fluid on a three-dimensional Riga plate with swimming microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Loganathan et al [29] utilized a third-grade fluid flow with nanoparticles with zero mass flux and a non-Fourier model to analyze entropy and heat transfer. With the assistance of Cattaneo-Christov dual diffusion, Loganathan et al [30] defined the effect of the hydrodynamic radiative Maxwell fluid model on a hot surface. Jamshed et al [31] investigated radiative Prandtl-Eyring hybrid nanofluid in a parabolic trough surface within a solar water pump to analyze the viscid dissipation, heat generation, and entropy.…”
Section: Introductionmentioning
confidence: 99%